Discrimination and Psychological Distress: Gender Differences among Arab Americans - Assari, Shervin; Lankarani, Maryam Moghani (Frontiers in Psychiatry, 2017)
Background: Despite the existing knowledge on the causal link between discrimination and poor mental health, very few studies have explored gender differences in this association in Arab Americans. Objective: The current study aimed to investigate gender differences in the association between discrimination and psychological distress in a representative sample of Arab Americans in Michigan. Methods: Using data from the Detroit Arab American Study (DAAS), 2003, this study recruited Arab Americans (337 male, 385 female) living in Michigan, United States. The main independent variable was discrimination. The main outcome was psychological distress. Covariates included demographic factors (age), socioeconomic status (education, employment, and income) and immigration characteristics (nativity and years living in U.S.). Gender was the focal moderator. We used multivariable regression with and without discrimination × gender interaction term. Results: In the pooled sample, discrimination was positively associated with psychological distress (B = 0.62, 95% CI = 0.22 - 1.03, p =0.003). We found a significant gender × discrimination interaction in the pooled sample (B = 0.79, 95% CI = 0.01 - 1.59, p =0.050), suggesting a stronger association in males than females. In our gender-specific model, higher discrimination was associated with higher psychological distress among male (B = 0.87, 95% CI = 0.33 - 1.42, p = 0.002) but not female (B = 0.18, 95% CI = -0.43-0.78, p =0.567) Arab Americans. Conclusion: While discrimination is associated with poor mental health, consequences may not be equally distributed among male and female Arab Americans, as documented by a stronger link between discrimination and psychological symptoms in men compared to women. While efforts should be made to universally reduce discrimination, screening for discrimination may be a more salient component of mental health care for male than female Arab Americans.